2004
DOI: 10.4049/jimmunol.173.3.1628
|View full text |Cite
|
Sign up to set email alerts
|

Lipid Raft-Associated GTPase Signaling Controls Morphology and CD8+ T Cell Stimulatory Capacity of Human Dendritic Cells

Abstract: Their eponymous morphology and unique ability to activate naive T cells are hallmark features of dendritic cells (DCs). Specific properties of the actin cytoskeleton may define both characteristics. In search for regulators that coordinate DC phenotype and function, we observed strongly increased expression of the actin-remodeling GTPases Cdc42 and Rac1 during DC development from human stem cells. Cdc42 and Rac1 are constitutively active in immature DCs, and their activity is further up-regulated by maturation… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
41
0

Year Published

2005
2005
2022
2022

Publication Types

Select...
10

Relationship

1
9

Authors

Journals

citations
Cited by 40 publications
(43 citation statements)
references
References 50 publications
1
41
0
Order By: Relevance
“…PUFAs were incorporated into DC membrane lipids in our studies and probably also in raft lipids since raft lipid alterations by exogenous fatty acids generally reflect those in cellular membranes (21). We did not detect any functional differences in early LPS-induced signaling events in PUFA-treated DCs though rafts could be involved in DC activation and LPS signal transduction as suggested by other studies (63,64). However, lipid raft-dependent LPS signaling in DCs has not yet been characterized in enough detail in order to completely understand a possible interference of PUFA with DC lipid raft signaling and its contribution to the inhibitory effects of PUFAs on DC activation.…”
Section: Discussionmentioning
confidence: 55%
“…PUFAs were incorporated into DC membrane lipids in our studies and probably also in raft lipids since raft lipid alterations by exogenous fatty acids generally reflect those in cellular membranes (21). We did not detect any functional differences in early LPS-induced signaling events in PUFA-treated DCs though rafts could be involved in DC activation and LPS signal transduction as suggested by other studies (63,64). However, lipid raft-dependent LPS signaling in DCs has not yet been characterized in enough detail in order to completely understand a possible interference of PUFA with DC lipid raft signaling and its contribution to the inhibitory effects of PUFAs on DC activation.…”
Section: Discussionmentioning
confidence: 55%
“…We have also demonstrated a high basal activity of 5-HT 7 R towards Cdc42 signaling in neuronal cells (Kvachnina et al, 2005), suggesting that both basal activity and agonist-mediated stimulation of the 5-HT 7 R-Cdc42 signaling pathway might contribute to morphological rearrangements of cells. Referring to dendritic cell morphology, Cdc42 has previously been shown to modulate cell shape changes by inducing alterations in the length and number of membrane protrusions, and it is required for the induction and maintenance of the typical stellate cytoskeletal architecture of mature dendritic cells (Jaksits et al, 2004;Nikolic et al, 2011;Swetman et al, 2002). Furthermore, it has been shown that Cdc42 deficiency induces a more rounded morphology in cultured cells (Chen et al, 2000;Wu et al, 2007).…”
Section: Discussionmentioning
confidence: 99%
“…The functional role of Rac1 and Cdc42 for the morphology and Ag-presenting capacity of DCs was described for DCs grown from hemopoietic stem cells (23) and PBMC-derived DC (24,25). Selective Rac1 inhibition in DCs was shown to diminish apoptotic cell uptake and cross-presentation in transgenic mice (26).…”
Section: Endritic Cells (Dc)mentioning
confidence: 99%